2021
DOI: 10.3389/fmicb.2020.614278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Dynamics and Volatile Metabolome Changes During Fermentation of Chambourcin Hybrid Grapes From Two Pennsylvania Regions

Abstract: Microbial diversity present on grapes in wineries, and throughout fermentation has been associated with important metabolites for final wine quality. Although microbiome-metabolome associations have been well characterized and could be used as indicators of wine quality, the impact of regionality on the microbiome and metabolome is not well known. Additionally, studies between microbiome and metabolome have been conducted on single species grape such as Vitis vinifera instead of other species and interspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 125 publications
(112 reference statements)
3
8
0
Order By: Relevance
“…In this work, 29 species were identified from 120 isolates and distinct patterns of microbial composition in three PA vineyards were observed. In support of a parallel study on Chambourcin microbiome, these results highlight unique differences in microbial populations even within a small geographic area (radius about 90 km) [60]. In 15 vineyards across southern Australia (5-400 km part), distinct microbial profiles were found in environmental samples collected from soil, plant, must, and across fermentation stages [61].…”
Section: Discussionsupporting
confidence: 71%
“…In this work, 29 species were identified from 120 isolates and distinct patterns of microbial composition in three PA vineyards were observed. In support of a parallel study on Chambourcin microbiome, these results highlight unique differences in microbial populations even within a small geographic area (radius about 90 km) [60]. In 15 vineyards across southern Australia (5-400 km part), distinct microbial profiles were found in environmental samples collected from soil, plant, must, and across fermentation stages [61].…”
Section: Discussionsupporting
confidence: 71%
“…Regarding the most abundant bacteria, microorganisms from the genus Pantoea were detected in all the sub-regions, enriched in QTX samples, and rapidly dominated the population after fermentation initiation ( Figure 5 a). Studies have shown that Pantoea is also a key feature in other wine regions, such as Penglai, Yangling, Shanshan, Yanqi, Heshuo, Huoerguosi, Fukang, and Manasi in China [ 25 , 27 ]; Minho, Douro, Dão, Bairrada, Estremadura, and Alentejo in Portuguese [ 8 ]; Modra in Slovakia [ 47 ]; Central Pennsylvania in the United States [ 48 ]; moreover, the Ullum Valley of San Juan Province in Argentina [ 49 ]. The predominant presence of this group is independent of the identification methods.…”
Section: Discussionmentioning
confidence: 99%
“…The wine microbiota profiles are affected by the grapevine, including vintages ( Oyuela Aguilar et al, 2020 ) and cultivar ( Bokulich et al, 2014 ; Pinto et al, 2015 ; Wang et al, 2021 ). Alpha and beta diversities showed that the bacterial community of the wine samples was less diverse compared to the soil samples.…”
Section: Discussionmentioning
confidence: 99%